The Urgency of Establishing Constitutional Court Procedural Law - Riyadi, Sugeng; Fauzan, Muhammad; Idamatussilmi, Idamatussilmi; Budiman, Asep (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2023)
The formulation of procedural law within the constitutional court is a crucial requirement, as stipulated by Article 24 C paragraph (6) of the 1945 Constitution of the Republic of Indonesia. While the Constitutional Court Procedural Law is outlined in Law No. 24 of 2003 on the Constitutional Court, it merely provides general points. Special aspects, aligned with individual case characteristics, are deferred to the Constitutional Court for independent regulation based on Article 86 and the Explanatory Note to Law No. 24 of 2003. However, this delegation is inappropriate as procedural law should be governed by Law-level regulations, not by Constitutional Court Regulations (PMK). To date, the Constitutional Court continues to produce the Procedural Law in the form of PMKs. This study employs a normative juridical research method, with a statutory and conceptual approach, and conducts analysis in a qualitative descriptive manner. This paper concludes, firstly, that the creation of procedural law within the constitutional court holds philosophical, juridical and sociological significance. Secondly, the drafting process of the constitutional court’s procedural law must adhere to the process of forming sound laws and regulations and contain materials in line with their level as prescribed in the legislation.